Decomposition of aged sedimentary organic matter in a deep temperate lake under warming conditions: An experimental approach - Wataru Nakamura; Yasuhiko T. Yamaguchi; Shish Muhammad Soyaib; Sho Ogasawara; Eiso Inoue; Koichi Shimotori; Yosuke Miyairi; Yusuke Yokoyama (Water Research, 2026)

Whole Mitochondrial Genome Analysis of Killer Whales Reveals the Presence of Resident and Transient Ecotypes Around Hokkaido - Momoka Suzuki; Mami Kawai; Takashi Hayakawa; Yuki F. Kita; Yu Sato; Miho Inoue‐Murayama; Akira Shiozaki; Shin Nishida; Shimpei F. Hiruta; Hiroshi Ohizumi; Fumio Nakahara; Shigeo Saino; et al. (Marine Mammal Science, 2026)
In the North Pacific, there are at least three genetically different ecotypes of killer whales ( Orcinus orca ), referred to as resident, offshore, and transient. A previous study suggested that killer whales around Hokkaido belong to fish‐eating (resident and/or offshore ecotypes) and mammal‐eating (transient ecotype) groups. These results were supported by haplotypes based on the combination of 1193 bp of cytochrome b and 420 bp of the control region in mitochondrial genomes. However, this analysis was not sufficient to discriminate between resident and offshore ecotypes because of the short sequence lengths. In this study, we analyzed whole mitochondrial genomes of 25 killer whales sampled around Hokkaido to clarify the ecotypes and mitochondrial genome haplotypes. Phylogenetic analysis revealed the presence of resident and transient ecotypes around Hokkaido. The whales identified as residents shared an identical haplotype, which is the most common haplotype in the western North Pacific. In contrast, the transients around Hokkaido exhibited eight haplotypes, including seven novel ones among the 19 individuals, and their haplotype richness was the highest among the North Pacific populations. This result suggests that the Hokkaido coast served as a refugium for transient killer whales during the Last Glacial Maximum.

Modelling free residual chlorine decay in a residential district water distribution network using smart water meter data - S. Obaid; K. Hosoi; N. M. Ngoc; T. Inoue; K. Yokota (International Journal of Environmental Science and Technology, 2025)
Chlorine is the most common disinfectant in drinking water worldwide, and the free residual chlorine concentration has been stipulated at least 0.1 mg/L according to Japanese drinking water standard to ensure disinfection efficacy during distribution. In addition, Japan is also applying approximately 0.4 mg/L chlorine at treatment plants to supply tasty drinkable water to residents. Although a concentration lower than 0.4 mg/L can help avoid an unpleasant chlorine taste in the supply water, it raises challenges for maintaining residual chlorine greater than the standard throughout distribution pipelines. The chlorine concentration decreases along distribution pipes because of bulk decay and wall decay. These decays depend on the initial chlorine concentration, temperature, time, pipe material, etc. Therefore, bottle tests with the Arrhenius theory were set up on the water at the distribution inlet in the Chibata district in Kosai city, Japan at various temperatures and times to measure the bulk decay coefficient. A literature review and root square mean error matching field data were conducted to estimate the wall decay coefficient. These decay coefficients were input into EPANET 2.2 to simulate water quality using smart water meters’ hourly consumption data. Therefore, the points where chlorine concentrations were below the standard could be hourly estimated.

P19-40 Risk assessment of AFB1 due to CYP3A4-mediated biotransformation with a highly sensitive human intestinal model - L. Bai; K. Tachibana; M. Murata; T. Inoue; H. Mizuguchi; S. Maeda; K. Ikemura; M. Okuda; T. Kusakabe; M. Kondoh (Toxicology Letters, 2024)

Preliminary analysis focusing on in-vessel thermal hydraulics in loss-of-heat removal systems in a sodium-cooled fast reactor - H. Sonoda; S. Fujita; M. Inoue; T. Okawa (Annals of Nuclear Energy, 2023)

Distribution of natural radionuclides in NORM samples from North Abu Rusheid area, Egypt - S. Sakr; K. Inoue; A. Mohamed; A.A. Ahmed; M.G. ElFeky; G.M. Saleh; M.S. Kamar; H. Arae; T. Aono; S.K. Sahoo (Journal of Environmental Radioactivity, 2023)

P25-22: Comparison of BMDL calculation performance by the recently developed Bayesian BMD calculation tools using quantal datasets of animal toxicity studies - A. Hirose; Y. Shigeta; T. Kawamura; K. Inoue; M. Matsumoto (Toxicology Letters, 2023)

P03-12: In vivo mutagenicity assessment and derivation of reference dose of styrene - Y. Murata; M. Matsumoto; T. Iso; Y. Shigeta; S. Hasegawa; T. Umano; N. Hirose; K. Horibata; K.-I. Sugiyama; K. Inoue; A. Hirose; K. Masumura (Toxicology Letters, 2023)

Genetic effects of demographic bottleneck and recovery in Kinkazan Island and mainland populations of Japanese macaques (Macaca fuscata) - N. Kazahari; E. Inoue; N. Nakagawa; Y. Kawamoto; T. Uno; M. Inoue-Murayama (Primates, 2023)

Correction: Anthocyanin synthesis potential in betalain-producing Caryophyllales plants - Masaaki Sakuta; Asuka Tanaka; Kaori Iwase; Mizuki Miyasaka; Sachiko Ichiki; Miho Hatai; Yoriko T. Inoue; Ayumi Yamagami; Takeshi Nakano; Kazuko Yoshida; Setsuko Shimada (Journal of Plant Research, 2022)

From Surface Water to the Deep Sea: A Review on Factors Affecting the Biodegradation of Spilled Oil in Marine Environment - Hernando Pactao Bacosa; Sheila Mae B. Ancla; Cris Gel Loui A. Arcadio; John Russel A. Dalogdog; Dioniela Mae C. Ellos; Heather Dale A. Hayag; Jiza Gay P. Jarabe; Ahl Jimhar T. Karim; Carl Kenneth P. Navarro; Mae Princess I. Palma; Rodolfo A. Romarate; Kaye M. Similatan; et al. (Journal of Marine Science and Engineering, 2022)
Over the past century, the demand for petroleum products has increased rapidly, leading to higher oil extraction, processing and transportation, which result in numerous oil spills in coastal-marine environments. As the spilled oil can negatively affect the coastal-marine ecosystems, its transport and fates captured a significant interest of the scientific community and regulatory agencies. Typically, the environment has natural mechanisms (e.g., photooxidation, biodegradation, evaporation) to weather/degrade and remove the spilled oil from the environment. Among various oil weathering mechanisms, biodegradation by naturally occurring bacterial populations removes a majority of spilled oil, thus the focus on bioremediation has increased significantly. Helping in the marginal recognition of this promising technique for oil-spill degradation, this paper reviews recently published articles that will help broaden the understanding of the factors affecting biodegradation of spilled oil in coastal-marine environments. The goal of this review is to examine the effects of various environmental variables that contribute to oil degradation in the coastal-marine environments, as well as the factors that influence these processes. Physico-chemical parameters such as temperature, oxygen level, pressure, shoreline energy, salinity, and pH are taken into account. In general, increase in temperature, exposure to sunlight (photooxidation), dissolved oxygen (DO), nutrients (nitrogen, phosphorous and potassium), shoreline energy (physical advection—waves) and diverse hydrocarbon-degrading microorganisms consortium were found to increase spilled oil degradation in marine environments. In contrast, higher initial oil concentration and seawater pressure can lower oil degradation rates. There is limited information on the influences of seawater pH and salinity on oil degradation, thus warranting additional research. This comprehensive review can be used as a guide for bioremediation modeling and mitigating future oil spill pollution in the marine environment by utilizing the bacteria adapted to certain conditions.

Pollution and contamination level of Cu, Cd, and Hg heavy metals in soil and food crop - Ramlan; M. Basir-Cyio; M. Napitupulu; T. Inoue; A. Anshary; Mahfudz; Isrun; M. Rusydi; Golar; Sulbadana; R. Bakri (International Journal of Environmental Science and Technology, 2022)
We aimed to assess and observe the accumulation of Cu, Cd, and Hg heavy metals on land and the contamination of plant tissues in Grand Forest Park, Palu, Indonesia, and its surrounding areas. The method used was a mix between survey and investigation, integrating data on research findings from before 2013 to 2016 with data from 2018. The data were analyzed using a correlation test, and descriptive statistics are presented in the form of tables and graphs. The results show that the highest concentration of Hg was found in the Poboya processing area (575.16 ppm) in 2013, though it gradually decreased to 287.64 ppm in 2018. The results of the Spearman’s rank test at the ∝ 0.05 level between average Cu land and Cu plant concentrations show that the obtained value ( r ) was 0.52 with a rho (ρ) of 0.13, which is not significant ( ρ 0.13 > 0.05), while for Cd and Hg metals, the obtained r values were 0.88 and 0.86, respectively. These two metals showed significant correlations between concentrations of Cd and Hg on land and Cd and Hg in plant tissues (both ρ 0.001 < 0.05). Specifically, the transfer factor (TF) value at the sampling sites of the Grand Forest Park area, Ngatabaru, and PBY from the average of various Hg concentrations in plants was much higher than the TF values of Cu and Cd, specifically being Hg > Cd = Cu or 0.61 > 0.17 = 0.17.

Eccrine sweat glands’ maximum ion reabsorption rates during passive heating in older adults (50–84 years) - N. Gerrett; T. Amano; Y. Inoue; Narihiko Kondo (European Journal of Applied Physiology, 2021)

Anthocyanin synthesis potential in betalain-producing Caryophyllales plants - Masaaki Sakuta; Asuka Tanaka; Kaori Iwase; Mizuki Miyasaka; Sachiko Ichiki; Miho Hatai; Yoriko T. Inoue; Ayumi Yamagami; Takeshi Nakano; Kazuko Yoshida; Setsuko Shimada (Journal of Plant Research, 2021)
Although anthocyanins are widely distributed in higher plants, betalains have replaced anthocyanins in most species of the order Caryophyllales. The accumulation of flavonols in Caryophyllales plants implies that the late step of anthocyanin biosynthesis from dihydroflavonols to anthocyanins may be blocked in Caryophyllales. The isolation and characterization of functional dihydroflavonol 4-reductase (DFR) and anthocyanidin synthase (ANS) from Caryophyllales plants has indicated a lack of anthocyanins due to suppression of DFR and ANS . In this study, we demonstrated that overexpression of DFR and ANS from Spinacia oleracea ( SoDFR and SoANS , respectively) with PhAN9 , which encodes glutathione S-transferase (required for anthocyanin sequestration) from Petunia induces ectopic anthocyanin accumulation in yellow tepals of the cactus Astrophytum myriostigma . A promoter assay of SoANS showed that the Arabidopsis MYB transcription factor PRODUCTION OF ANTHOCYANIN PIGMENT1 (PAP1) activated the SoANS promoter in Arabidopsis leaves. The overexpression of Arabidopsis transcription factors with PhAN9 also induced ectopic anthocyanin accumulation in yellow cactus tepals. PAP homologs from betalain-producing Caryophyllales did not activate the promoter of ANS . In-depth characterization of Caryophyllales PAPs and site-directed mutagenesis in the R2R3–MYB domains identified the amino acid residues affecting transactivation of Caryophyllales PAPs. The substitution of amino acid residues recovered the transactivation ability of Caryophyllales PAPs. Therefore, loss of function in MYB transcription factors may suppress expression of genes involved in the late stage of anthocyanin synthesis, resulting in a lack of anthocyanin in betalain-producing Caryophyllales plants.

Nanopore sequencing of tomato mottle leaf distortion virus, a new bipartite begomovirus infecting tomato in Brazil - Thais P. Martins; Tadeu A. Souza; Patricia S. da Silva; Erich Y. T. Nakasu; Fernando L. Melo; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2021)

Biodegradation of binary mixtures of octane with benzene, toluene, ethylbenzene or xylene (BTEX): insights on the potential of Burkholderia, Pseudomonas and Cupriavidus isolates - Hernando P. Bacosa; Jhonamie A. Mabuhay-Omar; Rodulf Anthony T. Balisco; Dawin M. Omar; Chihiro Inoue (World Journal of Microbiology and Biotechnology, 2021)

New microsatellite markers for Ellipse, Venustaconcha ellipsiformis (Bivalvia: Unionidae), with notes on optimal sample size and cross-species amplification - Kentaro Inoue; Bernard E. Sietman; Stephen E. McMurray; J. Scott Faiman; David T. Zanatta (Molecular Biology Reports, 2021)

Enhanced vertical turbulent nitrate flux in the intermediate layer of the Kuroshio in the Tokara Strait - T. Tanaka; D. Hasegawa; I. Yasuda; D. Yanagimoto; S. Fujio; H. Nakamura; R. Inoue; J. Nishioka (Journal of Oceanography, 2021)

Complete genome sequence of a new bipartite begomovirus infecting tomato in Brazil - Camila M. Rego-Machado; Erich Y. T. Nakasu; Rosana Blawid; Tatsuya Nagata; Alice K. Inoue-Nagata (Archives of Virology, 2019)

The influence of local skin temperature on the sweat glands maximum ion reabsorption rate - N. Gerrett; T. Amano; G. Havenith; Y. Inoue; Narihiko Kondo (European Journal of Applied Physiology, 2019)

Erratum to: Discovery of two small circular ssDNA viruses associated with the whitefly Bemisia tabaci - Erich Y. T. Nakasu; Fernando L. Melo; Miguel Michereff-Filho; Tatsuya Nagata; Bergmann M. Ribeiro; Simone G. Ribeiro; Cristiano Lacorte; Alice K. Inoue-Nagata (Archives of Virology, 2017)

Discovery of two small circular ssDNA viruses associated with the whitefly Bemisia tabaci - Erich Y. T. Nakasu; Fernando L. Melo; Miguel Michereff-Filho; Tatsuya Nagata; Bergmann M. Ribeiro; Simone G. Ribeiro; Cristiano Lacorte; Alice K. Inoue-Nagata (Archives of Virology, 2017)

Factors affecting water availability for high Arctic lichens - T. Inoue; S. Kudoh; M. Uchida; Y. Tanabe; M. Inoue; H. Kanda (Polar Biology, 2017)

Relating food and human hair to assess mercury exposure levels in Poboya, Central Sulawesi, Indonesia - M. M. Sari; T. Inoue; Y. Matsumoto; K. Yokota (International Journal of Environmental Science and Technology, 2017)

Screening for potentially hazardous PRTR chemicals in the Lake Biwa-Yodo River basin of Japan using a one-box multimedia model - B. H. A. K. T. Ariyadasa; Akira Kondo; Yoshio Inoue (Environmental Science and Pollution Research, 2015)

Complete genome sequence of pepper yellow mosaic virus, a potyvirus, occurring in Brazil - N. Lucinda; W. B. da Rocha; A. K. Inoue-Nagata; T. Nagata (Archives of Virology, 2012)

Association of root water-uptake ability with drought adaptation in wheat - M. Mori; M. Inagaki; T. Inoue; M. Nachit (Cereal Research Communications, 2011)

Audit and improve! Evaluation of a real-time probe-based PCR assay with internal control for the direct detection of Mycobacterium tuberculosis complex - M. Inoue; W. Y. Tang; S. Y. Wee; T. Barkham (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Seasonal Changes of PFOS and PFOA Concentrations in Lake Biwa Water - T. Tsuda; A. Inoue; T. Igawa; K. Tanaka (Bulletin of Environmental Contamination and Toxicology, 2010)

Enhanced Inhibitory Effects of TBT Chloride on the Development of F1 Rats - H. Asakawa; M. Tsunoda; T. Kaido; M. Hosokawa; C. Sugaya; Y. Inoue; Y. Kudo; T. Satoh; H. Katagiri; H. Akita; M. Saji; M. Wakasa; et al. (Archives of Environmental Contamination and Toxicology, 2010)

Pesticides in Water and Sediment from Littoral Area of Lake Biwa - T. Tsuda; T. Nakamura; A. Inoue; K. Tanaka (Bulletin of Environmental Contamination and Toxicology, 2009)

Pesticides in Water, Fish and Shellfish from Littoral Area of Lake Biwa - T. Tsuda; T. Nakamura; A. Inoue; K. Tanaka (Bulletin of Environmental Contamination and Toxicology, 2009)

Brugmansia suaveolens mottle virus, a novel potyvirus causing leaf mottling of Brugmansia suaveolens in Brazil - N. Lucinda; T. Nagata; A. K. Inoue-Nagata; R. B. Salaroli; E. W. Kitajima (Archives of Virology, 2008)

Turnip yellow mosaic virus isolated from Chinese cabbage in Japan - Namiko Kirino; Koji Inoue; Koji Tanina; Yuya Yamazaki; Satoshi T. Ohki (Journal of General Plant Pathology, 2008)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Reflectance characteristics of major land surfaces in slash‐and‐burn ecosystems in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2008)

Effects of nimesulide, a cyclooxygenase-2 selective inhibitor, on colitis induced tumors - T. Inoue; I. Hirata; M. Murano (Inflammopharmacology, 2008)

Traceability of slash‐and‐burn land‐use history using optical satellite sensor imagery: a basis for chronosequential assessment of ecosystem carbon stock in Laos - Y. Inoue; J. Qi; A. Olioso; Y. Kiyono; T. Horie; H. Asai; K. Saito; Y. Ochiai; T. Shiraiwa; L. Douangsavanh (International Journal of Remote Sensing, 2007)

Natural infection of Alternanthera tenella (Amaranthaceae) by a new potyvirus - A. M. R. Almeida; C. Y. Fukushigue; F. Sartori; E. Binneck; S. R. R. Marin; A. K. Inoue-nagata; C. M. Chagas; E. R. Souto; T. Mituti (Archives of Virology, 2007)

Evolutionary trend of phylogenetic diversity of nitrogen fixation genes in the gut community of wood‐feeding termites - A. YAMADA; T. INOUE; S. NODA; Y. HONGOH; M. OHKUMA (Molecular Ecology, 2007)
Nitrogen fixation by gut microorganisms is one of the crucial aspects of symbiosis in wood‐feeding termites since these termites thrive on a nitrogen‐poor diet. In order to understand the evolution of this symbiosis, we analysed the nitrogenase structural gene nifH in the gut microbial communities. In conjunction with the published sequences, we compared approximately 320 putatively functional NifH protein sequences obtained from a total of 19 termite samples that represent all the major branches of their currently proposed phylogeny, and from one species of the cockroach Cryptocercus that shares a common ancestor with termites. Using multivariate techniques for clustering and ordination, a phylogeny of NifH protein sequences was created and plotted variously with host termite families, genera, and species. Close concordance was observed between NifH communities and the host termites at genus level, but family level relationships were not always congruent with accepted termite clade structure. Host groups examined included basal families (Mastotermitidae, Termopsidae, Kalotermitidae, as well as Cryptocercus ), the most derived lower termite family Rhinotermitidae, and subfamilies representing the advanced and highly diverse apical family Termitidae (Macrotermitinae, Termitinae, and Nasutitermitinae). This selection encompassed the major nesting and feeding styles recognized in termites, and it was evident that NifH phylogenetic divergence, as well as the occurrence of alternative nitrogenase‐type NifH, was to some extent dependent on host lifestyle as well as phylogenetic position.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Oscillatory behavior of monsoon rainfall over Sri Lanka during the late 19th and 20th centuries and its relationships to SSTs in the Indian Ocean and ENSO - B. A. Malmgren; R. Hullugalla; G. Lindeberg; Y. Inoue; Y. Hayashi; T. Mikami (Theoretical and Applied Climatology, 2007)

Cospeciation in the triplex symbiosis of termite gut protists ( Pseudotrichonympha spp.), their hosts, and their bacterial endosymbionts - S. NODA; O. KITADE; T. INOUE; M. KAWAI; M. KANUKA; K. HIROSHIMA; Y. HONGOH; R. CONSTANTINO; V. UYS; J. ZHONG; T. KUDO; M. OHKUMA (Molecular Ecology, 2007)
A number of cophylogenetic relationships between two organisms namely a host and a symbiont or parasite have been studied to date; however, organismal interactions in nature usually involve multiple members. Here, we investigated the cospeciation of a triplex symbiotic system comprising a hierarchy of three organisms — termites of the family Rhinotermitidae, cellulolytic protists of the genus Pseudotrichonympha in the guts of these termites, and intracellular bacterial symbionts of the protists. The molecular phylogeny was inferred based on two mitochondrial genes for the termites and nuclear small‐subunit rRNA genes for the protists and their endosymbionts, and these were compared. Although intestinal microorganisms are generally considered to have looser associations with the host than intracellular symbionts, the Pseudotrichonympha protists showed almost complete codivergence with the host termites, probably due to strict transmissions by proctodeal trophallaxis or coprophagy based on the social behaviour of the termites. Except for one case, the endosymbiotic bacteria of the protists formed a monophyletic lineage in the order Bacteroidales, and the branching pattern was almost identical to those of the protists and the termites. However, some non‐codivergent evolutionary events were evident. The members of this triplex symbiotic system appear to have cospeciated during their evolution with minor exceptions; the evolutionary relationships were probably established by termite sociality and the complex microbial community in the gut.

Fluctuating serotonergic function in premenstrual dysphoric disorder and premenstrual syndrome: findings from neuroendocrine challenge tests - Y. Inoue; T. Terao; N. Iwata; K. Okamoto; H. Kojima; T. Okamoto; R. Yoshimura; J. Nakamura (Psychopharmacology, 2006)

Synchrotron IR study of hydrous ringwoodite (γ-Mg2SiO4) up to 30 GPa - E. M. Chamorro Pérez; I. Daniel; J.-C. Chervin; P. Dumas; J. D. Bass; T. Inoue (Physics and Chemistry of Minerals, 2006)

Mechanism of plasma glutathione peroxidase production in bovine adipocytes - Tadashi Yamasaki; Koji Tahara; Shoichi Takano; Miho Inoue-Murayama; Michael T. Rose; Takeshi Minashima; Hisashi Aso; Shin’ichi Ito (Cell and Tissue Research, 2006)

The Monitoring of Insects to Maintain Biodiversity in Ogawa Fores Reserve - S. Makino; H. Goto; T. Inoue; M. Sueyoshi; K. Okabe; M. Hasegawa; K. Hamaguchi; H. Ctanaka; I. Okochi (Environmental Monitoring and Assessment, 2006)

Expression of foreign type I ribulose-1,5-bisphosphate carboxylase/ oxygenase (EC 4.1.1.39) stimulates photosynthesis in cyanobacterium Synechococcus PCC7942 cells - T. Iwaki; K. Haranoh; N. Inoue; K. Kojima; R. Satoh; T. Nishino; S. Wada; H. Ihara; S. Tsuyama; H. Kobayashi; A. Wadano (Photosynthesis Research, 2006)

High incidence of elevated antibody titers to Epstein-Barr virus in patients with uveitis - C. Touge; H. Agawa; T. Sairenji; Y. Inoue (Archives of Virology, 2006)

The phase boundary between wadsleyite and ringwoodite in Mg2SiO4 determined by in situ X-ray diffraction - T. Inoue; T. Irifune; Y. Higo; T. Sanehira; Y. Sueda; A. Yamada; T. Shinmei; D. Yamazaki; J. Ando; K. Funakoshi; W. Utsumi (Physics and Chemistry of Minerals, 2006)

Face-selective and auditory neurons in the primate orbitofrontal cortex - Edmund T. Rolls; Hugo D. Critchley; Andrew S. Browning; Kazuo Inoue (Experimental Brain Research, 2006)

Characterization of two cytochrome oxidase operons in the marine cyanobacterium Synechococcus sp. PCC 7002: Inactivation of ctaDI affects the PS I:PS II ratio - Christopher T. Nomura; Søren Persson; Gaozhong Shen; Kaori Inoue-Sakamoto; Donald A. Bryant (Photosynthesis Research, 2006)

Intracolony variation of bacterial gut microbiota among castes and ages in the fungus‐growing termite Macrotermes gilvus - Y. HONGOH; L. EKPORNPRASIT; T. INOUE; S. MORIYA; S. TRAKULNALEAMSAI; M. OHKUMA; N. NOPARATNARAPORN; T. KUDO (Molecular Ecology, 2006)
The fungus‐growing termites Macrotermes cultivate the obligate ectosymbiontic fungi, Termitomyces . While their relationship has been extesively studied, little is known about the gut bacterial symbionts, which also presumably play a crucial role for the nutrition of the termite host. In this study, we investigated the bacterial gut microbiota in two colonies of Macrotermes gilvus , and compared the diversity and community structure of bacteria among nine termite morphotypes, differing in caste and/or age, using terminal restriction fragment length polymorphism (T‐RFLP) and clonal analysis of 16S rRNA. The obtained molecular community profiles clustered by termite morphotype rather than by colony, and the clustering pattern was clearly more related to a difference in age than to caste. Thus, we suggest that the bacterial gut microbiota change in relation to the food of the termite, which comprises fallen leaves and the fungus nodules of Termitomyces in young workers, and leaves degraded by the fungi, in old workers. Despite these intracolony variations in bacterial gut microbiota, their T‐RFLP profiles formed a distinct cluster against those of the fungus garden, adjacent soil and guts of sympatric wood‐feeding termites, implying a consistency and uniqueness of gut microbiota in M. gilvus . Since many bacterial phylotypes from M. gilvus formed monophyletic clusters with those from distantly related termite species, we suggest that gut bacteria have co‐evolved with the termite host and form a microbiota specific to a termite taxonomic and/or feeding group, and furthermore, to caste and age within a termite species.

Pharmacokinetics and pharmacodynamics of etizolam are influenced by polymorphic CYP2C19 activity - T. Fukasawa; N. Yasui–Furukori; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2005)

High-temperature and high-pressure equation of state for the hexagonal phase in the system NaAlSiO4 – MgAl2O4 - T. Shinmei; T. Sanehira; D. Yamazaki; T. Inoue; T. Irifune; K. Funakoshi; A. Nozawa (Physics and Chemistry of Minerals, 2005)

High prevalence of hepatitis B, C and delta virus infections among blood donors in Mongolia - B. Tsatsralt-Od; M. Takahashi; T. Nishizawa; J. Inoue; D. Ulaankhuu; H. Okamoto (Archives of Virology, 2005)

Comparison of Expression of Glucokinase Gene and Activities of Enzymes Related to Glucose Metabolism in Livers between Dog and Cat - A. Tanaka; A. Inoue; A. Takeguchi; T. Washizu; M. Bonkobara; T. Arai (Veterinary Research Communications, 2005)

Effect of skin temperature on the ion reabsorption capacity of sweat glands during exercise in humans - A. K. M. Shamsuddin; T. Kuwahara; A. Oue; C. Nomura; S. Koga; Y. Inoue; N. Kondo (European Journal of Applied Physiology, 2005)

Roles of Volume-sensitive Cl− Channel in Cisplatin-induced Apoptosis in Human Epidermoid Cancer Cells - T. Ise; T. Shimizu; E.L. Lee; H. Inoue; K. Kohno; Y. Okada (The Journal of Membrane Biology, 2005)

Effect of the protein kinase C inhibitor, staurosporine, on the high dose of methamphetamine-induced behavioral sensitization to dizocilpine (MK-801) - Y. R. Fang; T. Abekawa; X. B. Li; Z. C. Wang; T. Inoue; T. Koyama (Psychopharmacology, 2005)

Induction of the metabolism of etizolam by carbamazepine in humans - S. Kondo; T. Fukasawa; N. Yasui-Furukori; T. Aoshima; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2005)

Findings through the AsiaFlux network and a view toward the future - S. Yamamoto; N. Saigusa; M. Gamo; Y. Fujinuma; G. Inoue; T. Hirano (Journal of Geographical Sciences, 2005)

A novel melon flexivirus transmitted by whitefly - T. Nagata; D. M. T. Alves; A. K. Inoue-Nagata; T.-Y. Tian; E. W. Kitajima; J. E. Cardoso; A. C. de vila (Archives of Virology, 2005)

Changes in Activities of Enzymes Related to Energy Metabolism in Peripheral Leukocytes of Fattening Steers - N. Kimura; I. Yoshimura; T. Sako; A. Inoue; K. Tadami; T. Arai (Veterinary Research Communications, 2005)

A novel antipsychotic, perospirone, has antiserotonergic and antidopaminergic effects in human brain: findings from neuroendocrine challenge tests - M. Iwakawa; T. Terao; A. Soya; H. Kojima; Y. Inoue; N. Ueda; R. Yoshimura; J. Nakamura (Psychopharmacology, 2004)

Inhibition of the metabolism of etizolam by itraconazole in humans: evidence for the involvement of CYP3A4 in etizolam metabolism - K. Araki; N. Yasui-Furukori; T. Fukasawa; T. Aoshima; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2004)

Characterization of Oita virus 296/1972 of Rhabdoviridae isolated from a horseshoe bat bearing characteristics of both lyssavirus and vesiculovirus - K. Tanaka; Y. Sato; S. Morikawa; D. Hayasaka; M. Moriyama; T. Ono; A. Yamada; T. Kurata; T. Iwasaki; S. Inoue; S. Kanai (Archives of Virology, 2004)

Character displacement in style length between pollinator-sharing Clerodendrum trichotomum and C. izuinsulare (Verbenaceae) - T. Miyake; K. Inoue (Plant Systematics and Evolution, 2003)

Tandem duplication of alkaline phosphatase genes and polymorphism in the intergenic sequence in Bombyx mori - M. Itoh; T. Inoue; Y. Kanamori; S. Nishida; M. Yamaguchi (Molecular Genetics and Genomics, 2003)

Involvement of microtubules in rhizoid differentiation of Spirogyra species - K. Yoshida; N. Inoue; S. Sonobe; T. Shimmen (Protoplasma, 2003)

The effects of histamine on the lipopolysaccharide-induced metallothionein-I mRNA expression in the mouse spleen - T. Inoue; M. Nakano; N. Oda; T. Yoneyama; Y. Okano; K. Onodera; H. Furuta; C. A. Sogawa; N. Sogawa (Inflammation Research, 2003)

Nucleotide sequences of the coat protein gene of potyviruses infecting Ornithogalum thyrsoides - S. Fuji; M. Inoue; H. Yamamoto; H. Furuya; H. Naito; T. Matsumoto (Archives of Virology, 2003)

In situ X-ray observations of phase transitions in MgAl 2 O 4 spinel to 40 GPa using multianvil apparatus with sintered diamond anvils - T. Irifune; H. Naka; T. Sanehira; T. Inoue; K. Funakoshi (Physics and Chemistry of Minerals, 2002)

Raman spectra of hydrous γ -Mg 2 SiO 4 at various pressures and temperatures - L. Liu; C.-C. Lin; T. P. Mernagh; T. Inoue (Physics and Chemistry of Minerals, 2002)

Effect of MS-153 on the development of behavioral sensitization to locomotion- and ataxia-inducing effects of phencyclidine - Abekawa T.; Honda M.; Ito K.; Inoue T.; Koyama T. (Psychopharmacology, 2002)

Evaluation of formation potential of trihalomethanes and mutagens due to chlorination of river water along the Kizu River in the Yodo River system in Japan - S. Sanukida; T. Nobukawa; M. Ichihara; H. Shima; K. Inoue; S. Nakachi (Limnology, 2001)

Determination of the phase boundary between ilmenite and perovskite in MgSiO 3 by in situ X-ray diffraction and quench experiments - K. Kuroda; T. Irifune; T. Inoue; N. Nishiyama; M. Miyashita; K. Funakoshi; W. Utsumi (Physics and Chemistry of Minerals, 2000)

Subsite-specific risk factors for hypopharyngeal and esophageal cancer (Japan) - T. Takezaki; M. Shinoda; S. Hatooka; Y. Hasegawa; S. Nakamura; K. Hirose; M. Inoue; N. Hamajima; T. Kuroishi; H. Matsuura; K. Tajima (Cancer Causes & Control, 2000)

Physiological significance of hyperpolarization-activated inward currents (I h) in smooth muscle cells from the circular layers of pregnant rat myometrium - K. Okabe; Y. Inoue; T. Kawarabayashi; H. Kajiya; F. Okamoto; H. Soeda (Pflügers Archiv - European Journal of Physiology, 1999)

Physiological significance of hyperpolarization-activated inward currents ( I h ) in smooth muscle cells from the circular layers of pregnant rat myometrium - K. Okabe; Y. Inoue; T. Kawarabayashi; H. Kajiya; F. Okamoto; H. Soeda (Pflügers Archiv - European Journal of Physiology, 1999)

Localization and ultrastructure of pulmonary dendritic cells during delayed-type hypersensitivity reactions in mice - T. Nishida; Kiyotoshi Inoue; Toshihiko Kato; Takashi Iwata; Hiroaki Kinoshita; Kenji Kaneda (Cell and Tissue Research, 1999)

Effects of itraconazole on the steady-state plasma concentrations of bromperidol and reduced bromperidol in schizophrenic patients - Hanako Furukori; T. Kondo; Norio Yasui; Koichi Otani; Noboru Tokinaga; Udai Nagashima; Sunao Kaneko; Yoshimasa Inoue (Psychopharmacology, 1999)

Nestmate recognition in the stingless bee Melipona panamica (Apidae, Meliponini) - T. Inoue; D. W. Roubik; T. Suka (Insectes Sociaux, 1999)

Mg-vacant structural modules and dilution of the symmetry of hydrous wadsleyite, β-Mg 2-x SiH 2x O 4 with 0.00≤x≤0.25 - Y. Kudoh; T. Inoue (Physics and Chemistry of Minerals, 1999)

PCR-based method for identifying the S-genotypes of Japanese pear cultivars - T. Ishimizu; K. Inoue; M. Shimonaka; T. Saito; O. Terai; S. Norioka (Theoretical and Applied Genetics, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Temperature- and capsaicin-sensitive nerve fibers in brown adipose tissue attenuate thermogenesis in the rat - T. Osaka; Akiko Kobayashi; Yoshio Namba; Osamu Ezaki; Shuji Inoue; Shuichi Kimura; Tai Hee Lee (Pflügers Archiv - European Journal of Physiology, 1998)

Dependence of short-latency ocular following and associated activity in the medial superior temporal area (MST) on ocular vergence - Y. Inoue; A. Takemura; K. Kawano; T. Kitama; F. A. Miles (Experimental Brain Research, 1998)

Viruses produced from complementary DNA of virulent and avirulent strains of swine vesicular disease viruses retain the in vivo and in vitro characteristics of the parental strain - T. Kanno; T. Inoue; D. Mackay; P. Kitching; S. Yamaguchi; J. Shirai (Archives of Virology, 1998)

An alternatively spliced form of the human CD94 gene - Hiroshi Furukawa; T. Yabe; Kaoru Watanabe; Ritsuko Miyamoto; Tatsuya Akaza; Kenji Tadokoro; Shigeto Tohma; Tetsufumi Inoue; Kazuhiko Yamamoto; Takeo Juji (Immunogenetics, 1998)

Tea and coffee consumption and the risk of digestive tract cancers: data from a comparative case-referent study in Japan - M. Inoue; K. Tajima; K. Hirose; N. Hamajima; T. Takezaki; T. Kuroishi; S. Tominaga (Cancer Causes & Control, 1998)

Effects of various factors including the CYP2D6 genotype and coadministration of flunitrazepam on the steady-state plasma concentrations of bromperidol and its reduced metabolite - A. Suzuki; K. Otani; K. Mihara; N. Yasui; T. Kondo; N. Tokinaga; H. Furukori; S. Kaneko; Y. Inoue; K. Hayashi (Psychopharmacology, 1998)

The major carotenoid in all known species of heliobacteria is the C 30 carotenoid 4,4′-diaponeurosporene, not neurosporene - S. Takaichi; Kazuhito Inoue; Mitsuhiro Akaike; Masami Kobayashi; Hirozo Oh-oka; Michael T. Madigan (Archives of Microbiology, 1997)

Cyclooxygenase inhibitors enhance the production of tissue inhibitor-1 of metalloproteinases (TIMP-1) and pro-matrix metalloproteinase 1 (proMMP-1) in human rheumatoid synovial fibroblasts - S. Takahashi; T. Inoue; M. Higaki; Y. Mizushima (Inflammation Research, 1997)

Interaction between carbamazepine and bromperidol - K. Otani; M. Ishida; N. Yasui; T. Kondo; K. Mihara; A. Suzuki; H. Furukori; S. Kaneko; Y. Inoue (European Journal of Clinical Pharmacology, 1997)

A possible hybrid zone in the Mytilus edulis complex in Japan revealed by PCR markers - K. Inoue; S. Odo; T. Noda; S. Nakao; S. Takeyama; E. Yamaha; F. Yamazaki; S. Harayama (Marine Biology, 1997)

Efficacy of an ultrashort-acting β-adrenoceptor blocker (ONO-1101) in attenuating cardiovascular responses to endotracheal intubation - A. Kitamura; A. Sakamoto; T. Inoue; R. Ogawa (European Journal of Clinical Pharmacology, 1997)

Full-length genomic sequence of a hepatitis C virus genotype 2c isolate (BEBE1) and the 2c-specific PCR primers - H. Nakao; H. Okamoto; H. Tokita; T. Inoue; H. Iizuka; G. Pozzato; S. Mishiro (Archives of Virology, 1996)

Restriction endonuclease mapping and molecular cloning of the human herpesvirus 6 variant B strain Z29 genome - G. J. Lindquester; N. Inoue; R. D. Allen; J. W. Castelli; F. R. Stamey; T. R. Dambaugh; J. J. O'Brian; R. M. Danovich; N. Frenkel; P. E. Pellett (Archives of Virology, 1996)

Identification of epitopes associated with different biological activities on the glycoprotein of vesicular stomatitis virus by use of monoclonal antibodies - S. Nagata; Y. Okamoto; T. Inoue; Y. Ueno; T. Kurata; J. Chiba (Archives of Virology, 1992)

Replication of rat coronavirus in a rat cell line, LBC - N. Hirano; K. Ono; Y. Sada; A. Inoue; T. Murakami; H. Takamaru (Archives of Virology, 1985)

Antigenic difference between intracellular and membrane antigens induced by herpesvirus of turkeys - M. Inoue; T. Mikami; H. Kodama; M. Onuma; H. Izawa (Archives of Virology, 1980)

Properties of virus associated with subacute myelo-optico-neuropathy - Yoko Nishibe; T. Kimura; Y. K. Inoue (Archives of Virology, 1973)

Clonal analysis of tumorigenesis of bovine adenovirus type 3 and isolation of a nontumorigenic variant - Y. Nishibe; T. Kimura; Y. K. Inoue (Archives of Virology, 1970)